Digital Literacy Education in Responding to Controversial Content: A Case Study of Alleged Blasphemy on Social Media - Damayanti, Natasyah Sri; Ilman SM, Andi Mujahidil; Abu Nawas, Sitti Syakirah (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
The increasing consumption of digital content has highlighted the importance of digital literacy education, particularly in dealing with controversial content. This research analyzes the case of the viral video 'Pastor Gilbert' on social media. The research method used is qualitative with a case study approach, referring to Jurgen Hubermas' communication theory. Data was obtained through content analysis of discussions that emerged on social media as well as public discussion forums. Pastor Gilbert's controversial statement that sparked public outrage shows the importance of understanding and verifying digital content. The research emphasizes that digital literacy equips individuals with the ability to critically assess content, mitigate disinformation, and participate in constructive discussions. Through analyzing responses on social media, the study reveals a spectrum of reactions based on varying levels of digital literacy, highlighting the need for comprehensive digital education. Effective digital literacy programs can encourage healthier public discourse, prevent conflict escalation and promote a more harmonious society. This study recommends the integration of digital literacy into formal education and community training programs to improve critical thinking, ethical communication and responsible use of social media. The findings suggest that improved digital literacy is essential for navigating and resolving religious controversies in the digital age